Preclinical Models of Overwhelming Sepsis Implicate the Neural System that Encodes Contextual Fear Memory - Patricio T Huerta; Sergio Robbiati; Tomás S Huerta; Anchal Sabharwal; Roseann Berlin; Maya Frankfurt; Bruce T Volpe (BMC, 2016)
Abstract Long-term sepsis survivors sustain cryptic brain injury that leads to cognitive impairment, emotional imbalance and Increased disability burden. Suitable animal models of sepsis, such as cecal ligation and puncture (CLP), have permitted the analysis of abnormal brain circuits that underlie post-septic behavioral phenotypes. For instance, we have previously shown that CLP-exposed mice exhibit impaired spatial memory together with depleted dendritic arbors and decreased spines in the apical dendrites of pyramidal neurons in the CA1 region of the hippocampus. Here we show that contextual fear conditioning, a form of associative memory for fear, is chronically disrupted in CLP mice when compared with sham-operated animals. We also find that excitatory neurons in the basolateral nucleus of the amygdala (BLA) and granule cells in the dentate gyrus (DG) display significantly fewer dendritic spines in the CLP group relative to the sham mice, although the dendritic arbors and gross morphology of the BLA and DG are comparable between the two groups. Moreover, the basal dendrites of CA1 pyramidal neurons are unaffected in CLP mice. Taken together, our data indicate that structural damage in the amygdalar-hippocampal network represents the neural substrate for impaired contextual fear memory in long-term sepsis survivors. Further, our data suggest that brain injury caused by overwhelming sepsis alters the stability of the synaptic connections involved in associative fear. These results likely have implications for the emotional imbalance observed in human sepsis survivors.